The implications of wage structure rigidity on human capital accumulation, economic growth and unemployment: A Schumpeterian approach to endogenous growth theory - Michael Nusser (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 1999)
The approach put forward in this article is based on Schumpeter`s idea of creative destruction, the competitive process by which entrepreneurs are always looking for new ideas that will render their rivals` ideas obsolete. I present a model in which the rate of economic growth is sensitive to the interactions between relative wage and human capital accumulation. Human capital is an important source of sustained growth. By focusing explicity on innovation as an economic activity with different economic causes and effects, this article tries to open the door to a deeper understanding of how labor market rigidity in the form of wage structure rigidity affects human capital accumulation, and thereby the long-run growth through their effects on economic agent`s incentives to engage in knowledge-producing (education) activities. New technological vintages make it necessary that workers must become reeducated in order to qualify as skilled workers with the new generation of technology. Wage structure rigidity limits the incentives of agents to accumulate and adjust their human capital. This will be harmful to growth and employment.
Keywords: J1; J2; J3; J6; O3; O4; 330; economic growth; human capital accumulation; innovation; labor market rigidity; unemployment; wage (structure) rigidity; Innovationswettbewerb; Lohnstruktur; Lohnrigidität; Bildungsinvestition; Neue Wachstumstheorie; Strukturelle Arbeitslosigkeit; Theorie